In Vitro Evaluation of Smear Layer Removal with Different Methods of Activation of 17% EDTA with Ultrasonic and Laser Activation: A Scan Electron Micrscope Study - Varghese, Ajil Aji; Vinaychandra, R; Vanaki, Shreya Shreenivas; Dhamodaran, Thokala; Jayachandran, Mrinalini; Antony, Reshma Ters (Journal of Neonatal Surgery, 2025)
Root canal therapy aims to eliminate irritants from the root canal system, and lasers are being studied as an alternative for disinfection and smear layer removal. The Er,Cr:YSGG (hard tissue) is an infrared laser that has been shown to effectively clean root canals. 17% EDTA is one of the common irrigant used for removal of smear layer by its chelating action. This study is done for a comparative evaluation of 17% EDTA in removing smear layer with ultrasonic and laser activation (Er,Cr :YSGG) with the control group being 17% EDTA with syringe irrigation).